MENINGKATKAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE QUESTION STUDENT HAVE (QSH) PADA SISWA KELAS IV SDN SAGA V TANGERANG BANTEN - Zerri Rahman Hakim (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2015)
The objectives of this research were to determine: 1) Students’ learning activities in social studies after using Question Student Have (QSH) in Cooperative Learning Model, 2) Students’ learning outcomes in social studies after using Question Student Have (QSH) in Cooperative Learning Model. The method used in this research is Classroom Action Research (CAR) with Stephen Kemmis and Mc. Taggart Model which consists of four stages, namely planning, implementation, observation and reflection. This study was conducted by the researcher in two cycles. Instruments used in this research are observational sheet, interview, and test in the last cycle. From the analysis of the data, the researcher found that there is an improvement in students’ learning outcomes. On the basic value, there was only 43,33% students who achieve the learning mastery. In the first cycle, the students who achieve the learning mastery were increased, it was about 30% from the basic value, it reached 73,33%. On the second cycle, the student who achieve the learning mastery were increased about 26,70% from the first cycle, become 100%. The same thing also happened to the students' learning activities. In the first cycle, students’ learning activities is 71,42% and on the second cycle, students’ learning activities were incrased about 21,43% from the first cycle, become 92,85%. Based on the analysis of data of this study it can be concluded that the use of Question Student Have (QSH) in Cooperative Learning Model can improve students’ learning outcomes and learning activities fourth grade students of SDN Saga V in social studies.Keywords: social studies learning outcomes, cooperative learning QSH type.